Anengkerr angkety = dreaming stories - Ngal Cook, Jack.; Green, Jenny; Batchelor Institute of Indigenous Tertiary Education (N.T.) (Batchelor, N.T. : Batchelor Press, 2007)
Annotation pending.
"This book and accompanying audio recording contain pictures and voices of Anmatyerr people from the Northern Territory of Australia. Before using this book and CD, readers should talk to Indigenous Australian community members and follow their advice about using these stories in the classroom, community or in a public forum"--Verso of T.p.
Digital content preserved
Keywords: Aboriginal Australians -- Folklore -- Juvenile literature; Anmatyerre language -- Juvenile literature; Anmatyerre (Australian people); Stories and motifs - Emu; Stories and motifs - Birds; Stories and motifs - Devils, monsters, evil spirits, hairy men, bunyips; Stories and motifs - Dingoes / dogs; Anmatyerre / Anmatyerr people (C8.1) (NT SF53-09); Anmatyerre / Anmatyerr language (C8.1) (NT SF53-09)